Advancing Educational Practices: Implementation of the Course Review Horay Learning Model in Elementary Schools - Sukandar, Warlan; Warsiah, Warsiah; Nurhayati, Nurhayati; AS, Fadly; Marsanda, Yola (International Journal of Elementary School, 2024)
Improving the quality of education is an inevitable challenge in the development of society. One approach to achieving this is by implementing innovative learning models. This research aims to investigate the implementation of the Course Review Horay Learning Model in Elementary Schools as an effort to improve educational practices. The research method used is classroom action research involving teachers and students in the learning change process. Over several cycles, data was collected through classroom observations, interviews, and student performance assessments. The course review model is applied with a focus on providing constructive feedback, collaboration between students, and the use of technology in learning. The research results showed a significant increase in student participation, concept understanding, and learning motivation. Teachers reported positive changes in classroom dynamics, increased student engagement, and implementation of more interactive learning strategies. Technological support in implementing the course review horay also makes a positive contribution to learning efficiency. This research provides new insights regarding the potential of the Course Review Horay Learning Model as an effective tool for overcoming challenges in learning in elementary schools. Practical implications and recommendations for further development are also discussed to create an educational environment that is progressive and responsive to the needs of today's students.